Handbook of Milk of Non‐Bovine Mammals 2006
DOI: 10.1002/9780470999738.ch8
|View full text |Cite
|
Sign up to set email alerts
|

Buffalo Milk Production

Abstract: This study was carried out to investigate the fly count during different periods of the day during fly season and to show the effect of fly annoyance on buffalo behaviour and milk production and to investigate the efficacy of Butox ®, a commercially available fly repellent in reducing fly numbers. Five Egyptian adult female buffalo cows,6 years old, were used in the study. Both fly count and fly avoidance behaviors were recorded for two weeks before application of Butox ® and for the same period after applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
3
0
3
Order By: Relevance
“…Condensed skimmed milk is usually used for increasing milk solids in ice cream, bakery goods and many other foods, Pandya and Khan (2008). However, its standard of specification is not reported in Pakistan, but several states require 20 or 27% total solids content.…”
Section: An-overview On Buffalo Condensed Milk and Its Products Withmentioning
confidence: 99%
See 1 more Smart Citation
“…Condensed skimmed milk is usually used for increasing milk solids in ice cream, bakery goods and many other foods, Pandya and Khan (2008). However, its standard of specification is not reported in Pakistan, but several states require 20 or 27% total solids content.…”
Section: An-overview On Buffalo Condensed Milk and Its Products Withmentioning
confidence: 99%
“…Survey has been conducted on traditional Indian milk products which included the products, Khoa-based sweets (Burfi), Chhana-based sweets (Rasagolla), concentrated sweets (Rabri, Kheer, Khurchan and Palpayasam), fermented sweets (Shrikhand), frozen milk sweets (Kulfi), coagulated products (Chhana, Paneer), other fermented products (Dahi, Lassi, Misti), fat rich products (Ghee, Makkhan) and other concentrated products (Khoa). He reported that analysis of different concentrated sweets (Rabri, Kheer, Khurchan) had great variation in composition of the samples collected from Delhi, Haryana and Bombay by (Akhtar, 2015;Pandya and Khan, 2008).…”
Section: An-overview On Buffalo Condensed Milk and Its Products Withmentioning
confidence: 99%
“…Buvolí mléko je v mnohém nutričně hodnotnější než kravské mléko, jak je patrné z tabulky č. 1 (Zicarelli, 2004, Pandya a Khan, 2006, Fox et al, 2016, Navrátilová a Gřondělová, 2018. Vysoký obsah nutrientů buvolího mléka přitahuje obrovskou pozornost mlékárenského průmyslu při výrobě různých typů mléčných výrobků (Han et al, 2007).…”
Section: úVodunclassified
“…Tabulka 1: Porovnání složení buvolího a kravského mléka (Zicarelli, 2004, Pandya a Khan, 2006, Fox et al, 2016 (Zicarelli, 2004, Pandya a Khan, 2006, Navrátilová a Gřondělová, 2018. Buvolí mléko obecně obsahuje vyšší koncentrace minerálních látek než mléko kravské, vyniká především vysokým obsahem vápníku (Verruma a Salgado, 1994, Spanghero a Susmel, 1996, Soliman, 2005, Ahmad et al, 2008, Abd El-Salam a El-Shibiny, 2011, Navrátilová a Gřondělová, 2018.…”
Section: úVodunclassified
“…The XOR level in milk differs recognizably during lactation. However, bovine milk contains significant levels of XOR (1.4-1.8 U/mg) as compared to goat (0.27 U/mg) and sheep (0.69 U/mg) milk and camel (nd) milk because enzyme molecules lack molybdenum (Mo ++ ) [115][116][117][118]. This level can be amplified by complementing the diet with Mo ++ [7].…”
Section: Xanthine Oxidoreductasementioning
confidence: 99%